An Analysis of The Implementation of 4C Skills in Islamic Religious Education and Character Education - Wahyuni, Nani; Laksana, Sigit Dwi; Arifin, Syamsul; Pamungkas, Sahril Dwi; Syahapala, Muhammad Azamuddin (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2024)
The integration of 4C skills (Critical Thinking, Communication, Collaboration, and Creativity) in Islamic Religious and Character Education remains underexplored. This study examines how teachers at SMAN 1 Ngawi and SMAS Karya Pembangunan Paron understand and implement 4C skills, focusing on conceptual understanding, integration strategies, and challenge mitigation. Employing a descriptive qualitative approach, data were collected through interviews, observations, and document analysis, then analyzed using the Miles, Huberman, and Saldana framework. Findings reveal that SMAN 1 Ngawi demonstrated systematic 4C integration through structured curriculum design and technology-enhanced learning, reflecting comprehensive conceptual understanding. Conversely, SMAS Karya Pembangunan Paron exhibited fundamental understanding with adapted strategies utilizing reflective discussions and contextual projects to compensate for technological constraints. Both institutions encountered distinct challenges addressed through strategic planning, differentiated assessment, collaborative environments, and community partnerships. This study concludes that successful 4C implementation requires conceptual mastery, context-responsive strategies, and systemic support mechanisms for enhancing educational quality.